Interaction of Different Cover Types and Planting Media Combination on Nutrient Uptake, Growth, and Photosynthesis Characteristics of Kepok Bananas (Musa Paradisiaca L.) During Acclimatization - Khairunnisa; Hardiansyah, Elan (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
Tissue culture techniques, in general, have four stages, which include induction, multiplication, root formation, and acclimatization. The acclimatization stage is the most critical stage that plants go through after coming out of the culture bottle, and different climatic conditions exist in the greenhouse and the field. Environmental conditions such as light intensity and planting media greatly affect the growth of kepok banana seedlings during the acclimatization period. This research was conducted at the UPTD Balai Induk Hortikultura Gedung Johor Medan from June to August 2024. The research uses a Split Plot Design with two factors. The first factor is the type of cover: a 12% UV plastic cover and a 75% shade net. The second factor consists of three levels of treatment of the combination of planting media, namely soil + vermicompost (2:1), soil + cocopeat (2:1), and soil + Baked husk (2:1). 12% UV plastic produces more volume and root length than 75% shade nets. The chlorophyll a level was higher than that of chlorophyll b in all treatment interactions except in the 12% UV plastic cover treatment and the combination of soil + vermicompost planting media. Nitrogen uptake with 12% UV plastic enclosure treatment was 31.94% higher than 75% shade net. The implication of this finding is the potential to utilize vermicompost as a planting media mixture at the acclimatization stage of kepok banana.